2021
DOI: 10.3390/cancers13184655
|View full text |Cite
|
Sign up to set email alerts
|

Discordance of PD-L1 Expression at the Protein and RNA Levels in Early Breast Cancer

Abstract: We aimed to assess if the discrepant prognostic information between Programmed Death Ligand 1 (PD-L1) protein versus mRNA expression in early breast cancer (BC) could be attributed to heterogeneity in its expression. PD-L1 protein and mRNA expression in BC tissue microarrays from two clinical patient cohorts were evaluated (105 patients; cohort 1: untreated; cohort 2: neoadjuvant chemotherapy-treated). Immunohistochemistry (IHC) with SP142, SP263 was performed. PD-L1 mRNA was evaluated using bulk gene expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…In the current studies, the PD-L1 expression could be detected using tissue biopsy and liquid biopsy (circulating tumor cells, CTCs) ( 13 , 16 ). However, because the spatial-temporal heterogeneity of PD-L1 expression is inevitable, the information needed for the selection of appropriate therapy is limited to a single biopsy at a specific point ( 17 19 ). CTCs exhibit the advantages of continuous assessment, low invasiveness, and interrogation of the overall tumor burden, rather than a specific area ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the current studies, the PD-L1 expression could be detected using tissue biopsy and liquid biopsy (circulating tumor cells, CTCs) ( 13 , 16 ). However, because the spatial-temporal heterogeneity of PD-L1 expression is inevitable, the information needed for the selection of appropriate therapy is limited to a single biopsy at a specific point ( 17 19 ). CTCs exhibit the advantages of continuous assessment, low invasiveness, and interrogation of the overall tumor burden, rather than a specific area ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…36 Similar findings of weak concordance between PD-L1 mRNA and protein expression have been reported in previous studies on early human breast cancer. 39 Factors such as post-translational modifications and heterogeneity within tumor tissues may contribute to the lack of correlation between PD-L1 mRNA and protein levels in CMCs.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently demonstrated that different methods yield discrepancies for immune infiltrate assessment [113]. This observation is of utmost importance, since previously non-reproducible results have compromised the potential clinical significance of explored biomarkers [7,8,18]. In this direction, efforts have been undertaken to standardize recommendations for mIHC/IF [38,114] and DSP [115] but several questions still need to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, single biomarker expression demonstrated only modest performance, because of analytical limitations and tumor immune microenvironment (TIME) biology. In the case of the widely studied biomarker, PD-L1, assessment exhibits great inter-observer variability, given the different antibodies, platforms and scoring systems that exist [18]. Besides this, PD-L1 is but one immune checkpoint and interactions within TIME are way more complex [19].…”
Section: Introductionmentioning
confidence: 99%